Infrared Dual-line Hanle diagnostic of the Coronal Vector Magnetic Field - Gabriel Ionel Dima; Jeffrey R Kuhn; Svetlana V Berdyugina; Svetlana V Berdyugina; Svetlana V Berdyugina (Frontiers in Astronomy and Space Sciences, 2016)
Measuring the coronal vector magnetic field is still a major challenge in solar physics. This is due to the intrinsic weakness of the field (e.g. ~4G at a height of 0.1Rsun above an active region) and the large thermal broadening of coronal emission lines. We propose using concurrent linear polarization measurements of near-infrared forbidden and permitted lines together with Hanle effect models to calculate the coronal vector magnetic field. In the unsaturated Hanle regime both the direction and strength of the magnetic field affect the linear polarization, while in the saturated regime the polarization is insensitive to the strength of the field. The relatively long radiative lifetimes of coronal forbidden atomic transitions implies that the emission lines are formed in the saturated Hanle regime and the linear polarization is insensitive to the strength of the field. By combining measurements of both forbidden and permitted lines, the direction and strength of the field can be obtained. For example, the SiX 1.4301 um line shows strong linear polarization and has been observed in emission over a large field-of-view (out to elongations of 0.5 Rsun. Here we describe an algorithm that combines linear polarization measurements of the SiX 1.4301 um forbidden line with linear polarization observations of the HeI 1.0830 um permitted coronal line to obtain the vector magnetic field. To illustrate the concept we assume the emitting gas for both atomic transitions is located in the plane of the sky. The further development of this method and associated tools will be a critical step towards interpreting the high spectral, spatial and temporal infrared spectro-polarimetric measurements that will be possible when the Daniel K. Inouye Solar Telescope (DKIST) is completed in 2019.